Effect of Achillea millefolium Distillate on Recovery Time in Patients with Gastroenteritis - Abdi; Adib-Hajbaghery; Sharif (Kashan University of Medical Sciences, 2016)
Background Some animal studies have reported that Achillea millefolium (A. millefolium) extract can affect intestinal movements in rats. However, no study is available on the effect of A. millefolium on recovery from gastroenteritis in human subjects. Objectives This study aimed to investigate the effect of A. millefolium on recovery from gastroenteritis in patients over 12 years old. Patients and Methods A randomized controlled trial was conducted on 44 patients with gastroenteritis. The patients were randomly assigned to two groups of 22 each. The control group received the usual treatments. In addition to the usual treatments, the intervention group received 0.5 mL/kg of A. millefolium distillate every 8 hours. The duration of recovery was recorded for both groups. Descriptive statistics, Chi-square, Fisher's exact test, and the t-test were used to compare the two groups. Results The mean duration of recovery in the group receiving A. millefolium distillate was 1.31 ± 0.71 days, while it was 1.86 ± 0.71 days in the control group (P = 0.015). Conclusions Adding A. millefolium distillate to the usual treatment for simple gastroenteritis was effective in shortening the recovery time.